Insect Visitors of Mango Inflorescence - Singh, K. P.; Singh, Gajendra (Indian Forester, 2003)
The number of insect species visiting the mango flowers during blooming stage revealed that the maximum number of insects belonged to the families Syrphidae , Muscidae and Calliphoridae of the order Diptera while the minimum number was recorded in the order Lepidoptera.